Greske kvinner, kropp og makt. Feltarbeid på kulter knyttet til kvinnesfæren som utgangspunkt for en dekonstruksjonistisk lesning av mannsideologier nå og før - Håland, Evy Johanne (Religionsvidenskabeligt Tidsskrift, 2012)
By taking the statements in ancient Greek sources produced by men literally, it has been claimed that ancient women’s religious activities were performed under male dominance, or ‘appropriated’. So was the female body. The article argues that these statements need to be reconsidered. Based on studies in the same ancient sources, combined with results from fieldworks carried out on contemporary Greek religious festivals, a comparison is made with similar ancient festivals through an analysis of the fertility-cult, which is important in the festivals. This is a useful way to try to consider the female part of society, since women are the central performers of the actual cult that plays an important role within the official male value-system. This is the value-system that the festivals and the society, which they refl ect, traditionally have been considered from. The absence of the female value-system leaves previous analyses one-sided and incomplete. Therefore, a comprehensive analysis requires the female point of view to be included. Hence, the article argues for the importance of changing our approach when working with ancient culture. Taking account of the female sphere, which still exists in Greece, provides us with a basis for considering the female part of society. But, by so doing, the offi cial male perspective, which is similar to the Western male perspective generally applied within Greek studies, has to be deconstructed.